Injectable magnesium oxychloride cement foam (MOCF) derived scaffolds for treatment of osteoporotic bone defects
By introducing Pickering blistering technology into magnesium oxychloride cement to generate porous structure MOCF scaffolds, the problem of slow degradation of bone cement materials in existing osteoporosis treatment is solved, and higher biological activity and osteogenesis induction are achieved, which significantly improves the bone defect repair effect.
Patent Information
- Application Number
- CN202380068060.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-26
- Filing Date
- 2023-09-25
- Publication Date
- 2025-05-02
AI Technical Summary
Calcium phosphate cement materials in existing osteoporosis treatments slow down in physiological conditions, leading to poor integration with new bone tissue and obstacles to new bone formation, while potentially causing inflammation.
A porous magnesium oxychloride cement (MOCF) scaffold generated by Pickering foaming technology has a graded microscopic and macroscopic pore structure. Pores are introduced during the MOC formation process through a one-step Pickering foaming technology to form an injectable and self-shaped three-dimensional porous structure.
The MOCF scaffold showed excellent operating performance, appropriate degradation rate and good mechanical properties, which effectively recruited mesenchymal stem cells and stimulated in situ bone formation, significantly improving biological activity and osteogenesis.
Smart Images

Figure CN119923377A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 410,185, filed on September 26, 2022, the entire disclosure of which is incorporated herein by reference in its entirety for all purposes. Background Art
[0003] With the aging of the global population, osteoporosis is a highly common health problem in today's society. In particular, the frequent osteoporosis-related fractures and the delayed healing process of such fractures have brought great pain to osteoporosis patients. Cement reinforcement has been widely used in the treatment of osteoporotic bone defects. The products currently used for clinical treatment are mostly based on calcium phosphate (CaP) cement (CPC), including hydroxyapatite and brushite. However, due to the slow degradation rate of CPC under physiological conditions, these materials can only be partially absorbed or slightly absorbed by the body. This slow degradation can cause poor integration with regenerated bone tissue and hinder the formation of new bone. Worse, inflammation may also occur due to long-term foreign implants.
[0004] Magnesium (Mg) cements have been proposed as promising alternatives to classic Ca-based cements. These Mg-based cements generally have faster dissolution rates and better ability to bond with natural bone than those seen with Ca-based cements. Even more encouragingly, the Mg ions (Mg 2+ ) can play a vital role in bone metabolism by activating bone tissue-specific cell responses and regulating immune responses. It has been shown that magnesium phosphate cement (MPC) stimulates specific cell responses and tissue responses and actively drives the bone remodeling process. However, the exothermic reaction associated with the hardening process of MPC can cause necrosis of surrounding tissues. In addition, the release of ammonia or ammonium ions from MPC (e.g., from glassy crystals) into the physiological environment may cause biocompatibility issues.
[0005] Magnesium oxychloride cement (MOC, xMg(OH)2·yMgCl2·zH2O), also known as Sorel cement, has received increasing attention as a bone graft material. Although MOC has been variously implemented as a building material in adhesives, flooring, and plasters, it has been losing its popularity in these civil engineering applications due to its poor water resistance and subsequent degradation. Surprisingly, these degradation trends provide a rationale for expanding the application of MOC in hard tissue engineering. In addition to the osteoinductive Mg ions eluted from the degraded MOC and that can induce osteogenesis and promote bone formation, 2+ In addition to ions, chloride ions (Cl -) can also play an important role in bone homeostasis and maintain dynamic balance in the physiological environment. In addition, MOC is characterized by a low exothermic setting process, high early strength and satisfactory plasticity, making it a suitable bone reinforcement material.
[0006] Although MOC has been intensively studied to develop manufacturing strategies for improved water resistance, mechanical strength, and crystalline phase composition in the production of ideal MOC-based building materials, studies on the use of MOC as an implantable scaffold to enhance bone recovery are rare. Tan et al. conducted a preliminary study to evaluate the feasibility of MOC for orthopedic applications by co-culturing bone marrow stem cells (BMSCs) with MOC materials (J. Biomed. Mater. Res. A103, (2015): 194). The results showed that MOC modified with orthophosphoric acid showed good physical properties (i.e., compressive strength and degradation kinetics) to become a bone graft material while supporting the attachment and growth of BMSCs. Later in 2019, Guan et al. studied the effects of micron-sized and nano-sized hydroxyapatite (μ-HA and n-HA) particles on the water resistance and biological properties of MOC in a preclinical rat tibial defect model (RSC Adv. 9, (2019): 38619). They found that the addition of HA could effectively improve the water resistance of MOC, thus leading to a reasonable in vivo absorption rate. Furthermore, the MOC / n-HA combination exhibited a more active osteogenic effect than the MOC / μ-HA combination.Notably, the MOC-based scaffolds presented in the reported work were all dense and non-porous, making it possible to hinder the entry of cells and tissues into the scaffolds.
[0007] Ideal cement-derived implants are expected to present hierarchical micropore and macroporous structures for cell and tissue attachment and entry and sufficient nutrient transport. Although nanopores and micropores can be easily generated during cement formation, macropores must be intentionally constructed. There are many available strategies for introducing macropores into cement scaffolds, including particle leaching, three-dimensional (3D) printing, foaming and emulsion templates. In these methods, foaming provides the benefit of avoiding the use of a large amount of pore formers and producing the two-stage porosity required for cement implants. When applied to cement scaffolds, foaming technology can also support the good injectability and in-situ self-shaping ability that can realize minimally invasive surgery.
[0008] To date, several foaming techniques have been successfully applied to the preparation of graded porous cements, including gas foaming, syringe foaming, and surfactant foaming. However, these reported studies involve multiple steps or require the participation of carefully selected biocompatible surfactant additives, thereby limiting clinical application. Therefore, more effective methods are needed to introduce such graded porosity into cement-based scaffolds without degrading mechanical and biological properties. The present disclosure addresses these needs and other needs by providing materials and methods associated with porous magnesium oxychloride cements used as bone repair scaffolds with several beneficial advantages. Summary of the invention
[0009] The present disclosure generally relates to magnesium oxychloride cement (MOC) foam (MOCF) derived three-dimensional (3D) porous scaffolds produced by introducing the Pickering foaming technique into a magnesium oxide (MgO)-magnesium chloride (MgCl2)-water (H2O) reaction system. The MOCF derived scaffolds provide several advantages that are particularly beneficial for the restoration of osteoporotic bone defects. In some embodiments, the provided materials and methods include light-burned MgO particles modified with trace amounts of propyl gallate. The modified particles are used as particle stabilizers to generate ultra-stable foams, while MgCl2 aqueous solution is used as a continuous phase. The in-situ curing of the provided materials can be carried out simultaneously via the reaction of MgO with the liquid phase, resulting in the formation of a hierarchical porous MOCF scaffold in one step.
[0010] The obtained MOCF scaffold can show the desired integration of micropores and macropores, excellent handling performance, suitable degradation rate and good mechanical properties. The provided MOCF scaffold can not only be used as a structural support, but also can be used for the cell architecture of the MOCF-derived scaffold and the Mg-rich scaffold. 2+ The in situ delivery of ionic osteogenic inductors recruits mesenchymal stem cells (MSCs) and stimulates in situ osteogenesis. A large amount of in vitro evidence has confirmed that the MOCF-derived scaffold disclosed herein has non-porous and superior bioactivity and osteogenic inductivity compared to commercially available non-porous calcium-deficient hydroxyapatite (CDHA) cement. These features make the disclosed materials and methods promising to become a substitute for CaP-based bone cement products for clinical applications (e.g., osteoporotic bone defect repair applications) and have significant therapeutic effects.
[0011] In one aspect, the present disclosure relates to a composition comprising magnesium oxide, magnesium chloride, a surface modifier and water. In some embodiments, the composition comprises 15wt% to 70wt% of the magnesium oxide, 2wt% to 10wt% of the magnesium chloride, 0.2wt% to 2wt% of the surface modifier, and 20wt% to 65wt% of the water. The surface modifier present in the composition modifies at least a portion of the magnesium oxide to produce particles in the form of Pickering foam sufficient to stabilize the composition. In some embodiments, the composition has the form of the homogeneous paste. In some embodiments, the composition has the form of a cement formed by curing the homogeneous paste such that the cement includes a plurality of micropores.
[0012] In another aspect, the present disclosure relates to a bone repair scaffold. The scaffold includes a cement as disclosed herein. In some embodiments, the scaffold further includes cells attached to the cement.
[0013] In another aspect, the present disclosure relates to a method for producing magnesium oxychloride cement. The method includes forming a mixture of magnesium oxide and a surface modifier dispersed in an aqueous magnesium chloride solution. The method also includes foaming the mixture under conditions sufficient to generate an aqueous foam. In some embodiments, the method also includes forming a homogenous paste from the aqueous foam. In some embodiments, the method also includes curing the homogenous paste to produce the magnesium oxychloride cement.
[0014] In another aspect, the present disclosure relates to a method for repairing a bone defect in an individual, wherein the method comprises implanting a bone repair scaffold as disclosed herein near the bone defect in the individual. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The present invention is a schematic diagram of manufacturing an injectable 3D porous magnesium oxychloride cement foam (MOCF) derived scaffold according to the provided embodiment and demonstrating preosteoblast-scaffold integration. First, an ultra-stable aqueous foam is manufactured via high-speed foaming, wherein MgO microparticles adsorbed with trace amounts of propyl gallate are used as particle stabilizers, and the MgCl2 aqueous solution is the liquid phase. The remaining additives are introduced into the ultra-stable foam to obtain a MOCF paste showing good injectability. After complete curing in the mold, a MOCF scaffold with graded porosity is obtained, in which clear cell infiltration of the scaffold and excellent cell-scaffold integration can be easily achieved.
[0016] Figure 2 is a schematic diagram of manufacturing MOCF slurry according to the provided embodiment.
[0017] Figure 3 These are photos taken during the measurement of the injectability of MOCF paste.
[0018] Figure 4 is a graph depicting the extrusion curve recorded during injection of the prepared MOCF paste via a 5-mL syringe.
[0019] Figure 5 is a graph depicting the changes in elastic modulus, viscous modulus, and viscosity obtained from rheological measurements of MOCF paste during the curing process.
[0020] Figure 6 A series of images demonstrating the cohesive properties of MOC paste are presented: (i) photograph of MOCF paste after injection into phosphate buffered saline (PBS) solution; (ii) schematic diagram of the components of MOCF paste; (iii-iv) photographs of MOCF paste after curing in PBS solution for 24 h; (v) scanning electron microscope (SEM) image of the cross-morphology of cured MOCF.
[0021] Figure 7 is a schematic diagram of fabricating a MOCF-derived scaffold via curing a MOCF paste in a mold according to provided embodiments.
[0022] Figure 8 SEM images showing the cross-shaped morphology of MOCF-derived scaffolds and graphs depicting the pore size distribution of MOCF scaffolds.
[0023] Fig. 9 is a SEM image of the cross-shaped morphology of calcium-deficient hydroxyapatite (CDHA) cement.
[0024] Fig.10 is a diagram showing the crystalline phase composition of MOCF-derived scaffolds.
[0025] Fig.11 is a diagram showing the crystal phase composition of CDHA cement.
[0026] Fig.12 is a graph depicting representative strain-stress curves obtained from compression testing of MOCF and CDHA before and after immersion in PBS for 8 weeks.
[0027] Fig.13 is a graph depicting the yield strength of MOCF and CDHA as calculated from strain-stress curves before and after 8 weeks of immersion in PBS (n=3). Quantitative data are presented as mean±SD. Two-way ANOVA with Sidak post hoc test was used. *P<0.05, **P<0.01.
[0028] Fig.14is a graph depicting the Young's modulus of MOCF and CDHA as calculated from strain-stress curves before and after 8 weeks of immersion in PBS (n=3). Quantitative data are presented as mean±SD. Two-way ANOVA with Sidak post hoc test was used. **P<0.01.
[0029] Fig.15 SEM images showing cross-morphological analysis of MOCF samples and CDHA samples before and after immersion in PBS for 8 weeks are presented.
[0030] Fig.16 is a graph depicting the pH changes of PBS soaking solutions for MOCF and CDHA during the first week of a 4-week degradation test (n=3). Quantitative data are presented as mean±SD.
[0031] Fig.17 is a graph depicting the ions (i.e., Mg) released in the PBS soaking solution for MOCF and CDHA during the first week of the 4-week degradation test. 2+ and Ca 2+ ) concentration (n=3).
[0032] Fig.18 is a graph depicting the weight loss curves of MOCF samples and CDHA samples after immersion in PBS solution during a 4-week degradation test (n=3). Quantitative data are expressed as mean±SD.
[0033] Fig.19 is a diagram showing the crystalline phase composition of the surface and interior of MOCF after soaking in PBS solution during a 4-week degradation test.
[0034] Fig. 20 are graphs showing the surface and internal crystalline phase compositions of CDHA after immersion in PBS solution during a 4-week degradation test.
[0035] Fig.21 Representative SEM images of MC3T3-E1 preosteoblastic cell lines cultured on MOCF scaffolds and CDHA scaffolds for 1 and 5 days.
[0036] Fig. 22 Figure 2 is a graph depicting the expansion area of MC3T3-E1 cells cultured on MOCF scaffolds and CDHA scaffolds for 1 day and 5 days (n=8). Quantitative data are expressed as mean ± SD. *P<0.05, **P<0.01, ***P<0.001. Two-way ANOVA with Sidak's post hoc test was used.
[0037] Fig.23Representative images showing Alizarin Red S (ARS) staining of MOCF scaffolds and CDHA scaffolds after 10 days of osteogenic induction of rat bone marrow mesenchymal stem cells (rBMSCs).
[0038] Fig.24 is a graph depicting the relative expression of Opn in rBMSCs after 3 and 10 days of osteogenic induction (n=3), revealing the in vitro osteogenic differentiation of cells after incubation in sample extracts of MOCF and CDHA. Quantitative data are expressed as mean ± SD. ***P<0.001. Two-way ANOVA with Sidak's post hoc test was used.
[0039] Fig.25 Graph depicting the relative expression of Sp7 in rBMSCs after 3 and 10 days of osteogenic induction (n=3), revealing in vitro osteogenic differentiation of cells after incubation in sample extracts of MOCF and CDHA. Quantitative data are expressed as mean ± SD. **P<0.01. Two-way ANOVA with Sidak's post hoc test was used.
[0040] Fig.26 Graph depicting the relative expression of Runx2 in rBMSCs after 3 and 10 days of osteogenic induction (n=3), revealing in vitro osteogenic differentiation of cells after incubation in sample extracts of MOCF and CDHA. Quantitative data are expressed as mean ± SD. Two-way ANOVA with Sidak's posthoc test was used.
[0041] Fig. 27 Representative radiographs of femurs implanted with MOCF or CDHA obtained 4 or 12 weeks after surgery. The distal femoral defect is marked by an arrow.
[0042] Fig.28 Representative micro-computed tomography (micro-CT) images of femoral defects in the MOCF and CDHA groups at 4 and 12 weeks after surgery are shown.
[0043] Fig.29Graph depicting the results of quantitative analysis of bone volume fraction (bone volume / total volume, BV / TV) at the defect site 4 and 12 weeks after surgery (n=3). All quantitative data are expressed as mean ± SD. Two-way ANOVA with Sidak's post hoc test was used.
[0044] Fig.30 is a graph depicting the results of quantitative analysis of bone mineral density (BMD) at the defect site 4 and 12 weeks after surgery (n=3). All quantitative data are expressed as mean±SD. Two-way ANOVA with Sidak's post hoc test was used.
[0045] Fig.31 Graph depicting the results of quantitative analysis of the number of trabeculae (Tb.N) at the defect site 4 and 12 weeks after surgery (n=3). All quantitative data are expressed as mean ± SD. *P<0.05. Two-way ANOVA with Sidak's post hoc test was used. DETAILED DESCRIPTION
[0046] I. Overview
[0047] The present disclosure provides a method for incorporating the Pickering foaming technique into the MOC formation process ( Figure 1 ) is an effective and simple strategy for manufacturing injectable three-dimensional (3D) porous magnesium oxychloride cement (MOC) foam (MOCF) derived scaffolds. The provided MOCF derived scaffold is particularly advantageous for treating osteoporotic bone defects. Through one-step Pickering foaming, both macroscopic pore structure and microscopic pore structure are produced in the scaffold to meet the basic requirements of allowing the scaffold to be used as a bone substitute for bone defect repair. The manufactured MOCF scaffold shows excellent handling performance in the paste state, while also showing sufficient load-bearing capacity after curing. Compared with traditional bone cement, calcium-deficient hydroxyapatite (CDHA), the provided porous MOCF scaffold shows a much higher biodegradation trend and better cell recruitment ability. In addition, the bioactive ions eluted from MOCF produce and maintain a biologically induced microenvironment, in which in vitro osteogenesis is significantly enhanced. In summary, these features give the materials and methods disclosed herein great potential to enhance osteoporotic bone regeneration as an alternative to the materials and methods of using existing calcium-based products. Furthermore, the present disclosure also provides a straightforward and efficient fabrication strategy for constructing bioscaffolds with customizable 3D pores to meet clinical needs for bone regeneration or other diverse applications.
[0048] I. Overview
[0049] The present disclosure provides a method for incorporating the Pickering foaming technique into the MOC formation process ( Figure 1 ) is an effective and simple strategy for manufacturing injectable three-dimensional (3D) porous magnesium oxychloride cement (MOC) foam (MOCF) derived scaffolds. The provided MOCF derived scaffold is particularly advantageous for treating osteoporotic bone defects. Through one-step Pickering foaming, both macroscopic pore structures and microscopic pore structures are produced in the scaffold to meet the necessary requirements, that is, to allow the scaffold to be used as a bone substitute for bone defect repair. The manufactured MOCF scaffold shows excellent handling properties in the paste state, while also showing sufficient load-bearing capacity after curing. Compared with traditional bone cement, calcium-deficient hydroxyapatite (CDHA), the provided porous MOCF scaffold has a much higher biodegradation trend and better cell recruitment ability. In addition, the bioactive ions eluted by MOCF produce and maintain a biologically induced microenvironment, in which in vitro bone generation is significantly enhanced. In summary, these features give the materials and methods disclosed herein great potential as an improved alternative to the materials and methods using existing calcium-based products for promoting osteoporotic bone regeneration. Furthermore, the present disclosure also provides a straightforward and efficient fabrication strategy to construct bioscaffolds with customizable 3D pores to meet clinical needs for bone regeneration or other various applications.
[0050] II. Composition
[0051] In one aspect, the present disclosure provides various magnesium oxychloride cement compositions, which generally comprise magnesium oxide, magnesium chloride, one or more surface modifiers, and water. In some embodiments, the composition comprises magnesium oxide, magnesium chloride, one or more surface modifiers, and water. In some embodiments, the composition consists of magnesium oxide, magnesium chloride, one or more surface modifiers, and water. In some embodiments, the composition consists essentially of magnesium oxide, magnesium chloride, one or more surface modifiers, and water. The specific combination and relative amounts of these components allow the composition to provide several surprising improvements in various important structural properties, mechanical properties, and biological properties. When the provided composition is used to make certain medical implants (most notably, a scaffold that can be used to treat osteoporotic bone defects), these improved properties are particularly advantageous.
[0052] The presence of a surface modifier in the provided composition allows the composition to form a Pickering foam under the conditions disclosed herein. A Pickering foam is a foam stabilized by solid particles adsorbed at the interface between the liquid phase and the gas phase of the foam. In the provided composition, the surface modifier acts on at least a portion of the magnesium oxide in the composition to produce particles of magnesium oxide capable of stabilizing the foam. When the stabilized foam or a homogenous paste form thereof is cured into cement, the bubbles of the foam create voids in the resulting cement, creating the desired cement pore characteristics that are beneficial for implant scaffold applications. Therefore, the characteristics and amount of the surface modifier in the composition are generally selected so that the surface modifier effectively modifies the magnesium oxide to produce particles sufficient for stabilizing the Pickering foam.
[0053] The compositions disclosed herein may each include only one type of surface modifier, or may include two or more different surface modifiers. In some embodiments, at least one surface modifier of the composition is a short-chain amphiphilic compound. In some embodiments, each surface modifier of the composition is a short-chain amphiphilic compound. In some embodiments, the surface modifier includes one or more gallic acid ester compounds or is composed of one or more gallic acid ester compounds. In some embodiments, the surface modifier includes one or more gallic acid alkyl esters or is composed of one or more gallic acid alkyl esters. In some embodiments, the surface modifier includes propyl gallate or is composed of propyl gallate. In some embodiments, the surface modifier includes gallic acid or is composed of gallic acid. In some embodiments, the surface modifier includes one or more straight-chain saturated fatty acids or is composed of one or more straight-chain saturated fatty acids. In some embodiments, the surface modifier includes caproic acid or is composed of caproic acid. In some embodiments, the surface modifier includes propyl gallate and caproic acid or is composed of propyl gallate and caproic acid. In some embodiments, the surface modifier comprises or consists of propyl gallate and gallic acid. In some embodiments, the surface modifier comprises or consists of caproic acid and gallic acid. In some embodiments, the surface modifier comprises or consists of propyl gallate, caproic acid, and gallic acid.
[0054] The combined amount of one or more surface modifiers in the composition can be selected so that the amount effectively modifies a sufficient portion of the magnesium oxide of the composition to produce sufficient particles to stabilize the Pickering foam form of the composition. The concentration of the surface modifier in the composition can be, for example, from about 0.2 wt% to about 2 wt%, for example, from about 0.2 wt% to about 1.2 wt%, from about 0.4 wt% to about 1.4 wt%, from about 0.6 wt% to about 1.6 wt%, from about 0.8 wt% to about 1.8 wt% or from about 1 wt% to about 2 wt%. In some embodiments, the surface modifier concentration in the composition is from about 0.4 wt% to about 1.3 wt%, for example, from about 0.4 wt% to about 0.9 wt%, from about 0.5 wt% to about 1 wt%, from about 0.6 wt% to about 1.1 wt%, from about 0.7 wt% to about 1.2 wt% or from about 0.8 wt% to about 1.3 wt%. In terms of lower limits, the concentration of the surface modifier in the composition can be, for example, at least about 0.2 wt%, for example, at least about 0.4 wt%, at least about 0.5 wt%, at least about 0.6 wt%, at least about 0.7 wt%, at least about 0.8 wt%, at least about 0.9 wt%, at least about 1 wt%, at least about 1.1 wt%, at least about 1.2 wt%, at least about 1.3 wt%, at least about 1.4 wt%, at least about 1.6 wt% or at least about 1.8 wt%. In terms of upper limits, the surface modifier concentration in the composition can be, for example, up to about 2 wt%, for example, up to about 1.8 wt%, up to about 1.6 wt%, up to about 1.4 wt%, up to about 1.3 wt%, up to about 1.2 wt%, up to about 1.1 wt%, up to about 1 wt%, up to about 0.9 wt%, up to about 0.8 wt%, up to about 0.7 wt%, up to about 0.6 wt%, up to about 0.5 wt%, or up to about 0.4 wt%. Higher surface modifier concentrations (e.g., greater than about 2 wt%) and lower surface modifier concentrations (e.g., less than about 0.2 wt%) are also contemplated.
[0055] The magnesium oxide content of the composition can be selected to provide sufficient magnesium oxide to be modified and to form sufficient particles to stabilize the Pickering foam form of the composition. Because the crystalline phase of magnesium oxychloride cement depends at least in part on the amount of magnesium oxide relative to the amount of magnesium chloride and water in the cement, and because the cement crystalline phase can affect important properties of the cement, the magnesium oxide content of the composition can also be selected to provide a cement formed from the composition having a desired crystalline phase content. Thus, the inventors have demonstrated this and other reasons why certain magnesium oxide concentrations provide favorable physical, mechanical and processing properties to the composition.
[0056] The concentration of magnesium oxide in the composition can be, for example, from about 15 wt% to about 70 wt%, for example, from about 15 wt% to about 48 wt%, from about 20.5 wt% to about 53.5 wt%, from about 26 wt% to about 59 wt%, from about 31.5 wt% to about 64.5 wt%, or from about 37 wt% to about 70 wt%. In some embodiments, the magnesium oxide concentration in the composition is from about 30 wt% to about 60 wt%, for example, from about 30 wt% to about 48 wt%, from about 33 wt% to about 51 wt%, from about 36 wt% to about 54 wt%, from about 39 wt% to about 57 wt%, or from about 42 wt% to about 60 wt%. In terms of lower limits, the magnesium oxide concentration in the composition can be, for example, at least about 15 wt%, for example, at least about 20.5 wt%, at least about 26 wt%, at least about 30 wt%, at least about 33 wt%, at least about 36 wt%, at least about 39 wt%, at least about 42 wt%, at least about 45 wt%, at least about 48 wt%, at least about 51 wt%, at least about 54 wt%, at least about 57 wt%, at least about 60 wt%, or at least about 64.5 wt%. In terms of upper limits, the magnesium oxide concentration in the composition can be, for example, up to about 70 wt%, for example, up to about 64.5 wt%, up to about 60 wt%, up to about 57 wt%, up to about 54 wt%, up to about 51 wt%, up to about 48 wt%, up to about 45 wt%, up to about 42 wt%, up to about 39 wt%, up to about 36 wt%, up to about 33 wt%, up to about 30 wt%, up to about 26 wt%, or up to about 20.5 wt%. Higher magnesium oxide concentrations (e.g., greater than about 70 wt%) and lower magnesium oxide concentrations (e.g., less than about 15 wt%) are also contemplated.
[0057] As with magnesium oxide, the inventors have also shown that the magnesium chloride content of the composition can be selected to provide a cement formed from a composition having a desired crystalline content and other advantageous physical, mechanical and processing properties. The concentration of magnesium chloride in the composition can be, for example, from about 2 wt% to about 10 wt%, for example, from about 2 wt% to about 6.8 wt%, for example, from about 2.8 wt% to about 7.6 wt%, from about 3.6 wt% to about 8.4 wt%, from about 4.4 wt% to about 9.2 wt%, or from about 5.2 wt% to about 10 wt%. In some embodiments, the magnesium chloride concentration in the composition is from about 4 wt% to about 8 wt%, for example, from about 4 wt% to about 6.4 wt%, from about 4.4 wt% to about 6.8 wt%, from about 4.8 wt% to about 7.2 wt%, from about 5.2 wt% to about 7.6 wt%, or from about 5.6 wt% to about 8 wt%. In terms of lower limits, the magnesium chloride concentration in the composition can be, for example, at least about 2 wt%, for example, at least about 2.8 wt%, at least about 3.6 wt%, at least about 4 wt%, at least about 4.4 wt%, at least about 4.8 wt%, at least about 5.2 wt%, at least about 5.6 wt%, at least about 6 wt%, at least about 6.4 wt%, at least about 6.8 wt%, at least about 7.2 wt%, at least about 7.6 wt%, at least about 8 wt%, at least about 8.4 wt%, or at least about 9.2 wt%. In terms of upper limits, the magnesium chloride concentration in the composition can be, for example, at most about 10 wt%, for example, at most about 9.2 wt%, at most about 8.4 wt%, at most about 8 wt%, at most about 7.6 wt%, at most about 7.2 wt%, at most about 6.8 wt%, at most about 6.4 wt%, at most about 6 wt%, at most about 5.6 wt%, at most about 5.2 wt%, at most about 4.8 wt%, at most about 4.4 wt%, at most about 4 wt%, at most about 3.6 wt%, or at most about 2.8 wt%. Higher magnesium chloride concentrations (e.g., greater than about 10 wt%) and lower magnesium chloride concentrations (e.g., less than about 2 wt%) are also contemplated.
[0058] The water content of composition can also be selected to provide cement formed by the composition with desired crystalline content and other favorable physical properties, mechanical properties and processing properties. The concentration of water in the composition can be, for example, about 20wt% to about 65wt%, for example, about 20wt% to about 47wt%, about 24.5wt% to about 51.5wt%, about 29wt% to about 56wt%, about 33.5wt% to about 60.5wt% or about 38wt% to about 65wt%. In some embodiments, water concentration is about 30wt% to about 55wt% in the composition, for example, about 30wt% to about 45wt%, about 32.5wt% to about 47.5wt%, about 35wt% to about 50wt%, about 37.5wt% to about 52.5wt% or about 40wt% to about 55wt%. In terms of lower limits, the water concentration in the composition can be, for example, at least about 20 wt%, for example, at least about 24.5 wt%, at least about 29 wt%, at least about 32.5 wt%, at least about 35 wt%, at least about 37.5 wt%, at least about 40 wt%, at least about 42.5 wt%, at least about 45 wt%, at least about 47.5 wt%, at least about 50 wt%, at least about 52.5 wt%, at least about 56 wt% or at least about 60.5 wt%. With regard to upper limits, water concentration in the composition can be, for example, at most about 65wt%, for example, at most about 60.5wt%, at most about 56wt%, at most about 52.5wt%, at most about 50wt%, at most about 47.5wt%, at most about 45wt%, at most about 42.5wt%, at most about 40wt%, at most about 37.5wt%, at most about 35wt%, at most about 32.5wt%, at most about 29wt% or at most about 24.5wt%. Higher water concentrations (e.g., greater than about 65wt%) and lower water concentrations (e.g., less than about 20wt%) are also contemplated.
[0059] It has been demonstrated that the particularly useful properties of the provided compositions are not only a result of the individual concentrations of the various components of the composition, but also a result of the amounts of the components relative to each other. For example, certain relative amounts of magnesium oxide relative to magnesium chloride provide the composition with its advantageous characteristics. The molar ratio of magnesium oxide in the composition to magnesium chloride in the composition can be, for example, from about 2.5:1 to about 15:1, for example, from about 2.5:1 to about 10:1, from about 3.75:1 to about 11.25:1, from about 5:1 to about 12.5:1, from about 6.25:1 to about 13.75:1, or from about 7.5:1 to about 15:1. In terms of lower limits, the molar ratio of magnesium oxide to magnesium chloride can be, for example, at least about 2.5:1, e.g., at least about 3.75:1, at least about 5:1, at least about 6.25:1, at least about 7.5:1, at least about 8.75:1, at least about 10:1, at least about 11.25:1, at least about 12.5:1, or at least about 13.75:1. In terms of upper limits, the molar ratio of magnesium oxide to magnesium chloride can be, for example, at most about 15:1, e.g., at most about 13.75:1, at most about 12.5:1, at most about 11.25:1, at most about 10:1, at most about 8.75:1, at most about 7.5:1, at most about 6.25:1, at most about 5:1, or at most about 3.75:1. Higher ratios (e.g., greater than about 15:1) and lower ratios (e.g., less than about 2.5:1) of magnesium oxide to magnesium chloride are also contemplated.
[0060] Certain relative amounts of water to magnesium chloride in the composition have also been demonstrated to provide the compositions disclosed herein with their surprisingly useful properties. The molar ratio of water in the composition to magnesium chloride in the composition can be, for example, from about 5:1 to about 25:1, for example, from about 5:1 to about 17:1, from about 7:1 to about 19:1, from about 9:1 to about 21:1, from about 11:1 to about 23:1, or from about 13 to about 25:1. In terms of lower limits, the molar ratio of water to magnesium chloride can be, for example, at least about 5:1, for example, at least about 7:1, at least about 9:1, at least about 11:1, at least about 13:1, at least about 15:1, at least about 17:1, at least about 19:1, at least about 21:1, or at least about 23:1. In terms of upper limits, the molar ratio of water to magnesium chloride can be, for example, at most about 25: 1, for example, at most about 23: 1, at most about 21: 1, at most about 19: 1, at most about 17: 1, at most about 15: 1, at most about 13: 1, at most about 11: 1, at most about 9: 1, or at most about 7: 1. Higher ratios (e.g., greater than about 25: 1) and lower ratios (e.g., less than about 5: 1) of water to magnesium chloride are also contemplated.
[0061] The compositions disclosed herein may also include one or more additional compounds shown to provide beneficial properties to the composition, such as increased mechanical strength and / or improved handling properties during processing or application. In some embodiments, such additives are introduced into the composition after the composition in the form of a Pickering foam has been formed. In some embodiments, one or more additives are introduced into the composition before or simultaneously with mixing the composition to generate a composition in the form of a homogenous paste.
[0062] In some embodiments, the composition further comprises one or more soluble phosphate compounds as additives. In some embodiments, the composition comprises phosphoric acid. In some embodiments, the composition comprises sodium dihydrogen phosphate. In some embodiments, the composition comprises disodium hydrogen phosphate. In some embodiments, the composition comprises phosphoric acid and sodium dihydrogen phosphate. In some embodiments, the composition comprises phosphoric acid and disodium hydrogen phosphate. In some embodiments, the composition comprises phosphoric acid, sodium dihydrogen phosphate, and disodium hydrogen phosphate.
[0063] The total concentration of one or more soluble phosphate compounds (when present in the composition) in the provided compositions can be, for example, from about 0.1 wt% to about 2 wt%, for example, from about 0.1 wt% to about 0.6 wt%, from about 0.15 wt% to about 0.8 wt%, from about 0.2 wt% to about 1.1 wt%, from about 0.25 wt% to about 1.5 wt%, or from about 0.35 wt% to about 2 wt%. In terms of lower limits, the concentration of soluble phosphate compounds in the composition can be, for example, at least about 0.1 wt%, for example, at least about 0.15 wt%, at least about 0.2 wt%, at least about 0.25 wt%, at least about 0.35 wt%, at least about 0.45 wt%, at least about 0.6 wt%, at least about 0.8 wt%, at least about 1.1 wt%, or at least about 1.5 wt%. In terms of upper limits, the soluble phosphate compound concentration in the composition can be, for example, at most about 2 wt%, for example, at most about 1.5 wt%, at most about 1.1 wt%, at most about 0.8 wt%, at most about 0.6 wt%, at most about 0.45 wt%, at most about 0.35 wt%, at most about 0.25 wt%, at most about 0.2 wt%, or at most about 0.15 wt%. Higher soluble phosphate compound concentrations (e.g., greater than about 2 wt%) and lower soluble phosphate compound concentrations (e.g., less than about 0.1 wt%) are also contemplated.
[0064] In some embodiments, the composition also includes one or more polymers as additives. Without being bound by a particular theory, the inventors believe that the polymer in the composition provided can play a role in making the inorganic substance of the composition crosslinked. This crosslinking can enhance the cohesive properties of the composition, allowing the composition to maintain a desired predetermined shape in an aqueous environment, while the composition is in the form of a paste and simultaneously undergoes solidification to form cement. In some embodiments, the composition includes one or more natural polymers. In some embodiments, the composition includes gelatin. In some embodiments, the composition includes chitosan. In some embodiments, the composition includes gelatin and chitosan.
[0065] The total concentration of one or more polymers such as gelatin and / or chitosan (when present in the composition) in the provided compositions can be, for example, from about 1 wt% to about 10 wt%, for example, from about 1 wt% to about 6.4 wt%, from about 1.9 wt% to about 7.3 wt%, from about 2.8 wt% to about 8.2 wt%, from about 3.7 wt% to about 9.1 wt%, or from about 4.6 wt% to about 10 wt%. In terms of lower limits, the polymer concentration in the composition can be, for example, at least about 1 wt%, for example, at least about 1.9 wt%, at least about 2.8 wt%, at least about 3.7 wt%, at least about 4.6 wt%, at least about 5.5 wt%, at least about 6.4 wt%, at least about 7.3 wt%, at least about 8.2 wt%, or at least about 9.1 wt%. In terms of upper limits, the polymer concentration in the composition can be, for example, at most about 10wt%, for example, at most about 9.1wt%, at most about 8.2wt%, at most about 7.3wt%, at most about 6.4wt%, at most about 5.5wt%, at most about 4.6wt%, at most about 3.7wt%, at most about 2.8wt% or at most about 1.9wt%. Higher polymer concentrations (e.g., greater than about 10wt%) and lower polymer concentrations (e.g., less than about 1wt%) are also contemplated.
[0066] In some embodiments, the composition provided also includes one or more calcium phosphate cements as additives. In addition to increasing the mechanical strength of the composition, calcium phosphate cement can allow the composition to advantageously elute calcium ions during degradation in vivo, further producing a biological induction microenvironment for supporting cell growth. In some embodiments, the composition includes calcium-deficient hydroxyapatite. In some embodiments, the composition includes hydroxyapatite. In some embodiments, the composition includes brushite. In some embodiments, the composition includes calcium-deficient hydroxyapatite and hydroxyapatite. In some embodiments, the composition includes calcium-deficient hydroxyapatite and brushite. In some embodiments, the composition includes hydroxyapatite and brushite. In some embodiments, the composition includes calcium-deficient hydroxyapatite, hydroxyapatite and brushite. In some embodiments, the composition includes calcium-deficient hydroxyapatite, hydroxyapatite and brushite. In some embodiments, the composition includes calcium-deficient hydroxyapatite, hydroxyapatite and brushite.
[0067] The total concentration of one or more calcium phosphate cements (when present in the composition) in the provided composition can be, for example, from about 10wt% to about 35wt%, for example, from about 10wt% to about 25wt%, from about 12.5wt% to about 27.5wt%, from about 15wt% to about 30wt%, from about 17.5wt% to about 32.5wt% or from about 20wt% to about 35wt%. With regard to lower limits, the calcium phosphate cement concentration in the composition can be, for example, at least about 10wt%, for example, at least about 12.5wt%, at least about 15wt%, at least about 17.5wt%, at least about 20wt%, at least about 22.5wt%, at least about 25wt%, at least about 27.5wt%, at least about 30wt% or at least about 32.5wt%. With regard to the upper limit, calcium phosphate cement concentration can be, for example, at most about 35wt% in the composition, for example, at most about 32.5wt%, at most about 30wt%, at most about 27.5wt%, at most about 25wt%, at most about 22.5wt%, at most about 20wt%, at most about 17.5wt%, at most about 15wt% or at most about 12.5wt%.Higher calcium phosphate cement concentration (for example, greater than about 35wt%) and lower calcium phosphate cement concentration (for example, less than about 10wt%) are also contemplated.
[0068] One of the advantages of the provided composition is that, because the composition can form a Pickering foam containing a plurality of stable bubbles, the foam in the form of a solidified cement contains a plurality of and various holes at the previous positions of those bubbles. The number and morphology of the holes have been shown to be highly advantageous for applications such as bone defect repair, where the holes support the attachment and entry of cells and the transport of nutrients to the defect site. Unlike other denser cements (e.g., calcium phosphate cements), the cement form of the provided composition includes not only nanopores, but also micropores and macropores (i.e., holes with a diameter greater than 10 μm). The percentage of a plurality of holes in the cement form of the provided compound with a diameter greater than 10 μm can be, for example, at least about 90%, for example, at least about 91%, at least about 92%, at least about 93%, at least about 94%, at least about 95%, at least about 96%, at least about 97%, at least about 98%, or at least about 99%. The percentage of multiple pores in the cement form of the provided compound having a diameter greater than 50 μm can be, for example, at least about 10%, for example, at least about 15%, at least about 20%, at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50% or at least about 55%.
[0069] Another advantage of the provided composition is that due to the specific amounts of magnesium oxide, magnesium chloride and water in the composition, a desired predetermined relative portion of 5-phase crystals in the composition can be obtained. Magnesium oxychloride cements produce different crystalline phases having the general formula xMg(OH)2·yMgCl2·zH2O based on the chemical reaction between their magnesium oxide, magnesium chloride and water components. The specific values of x, y and z in the formula depend at least in part on the initial molar ratio of the three precursor components. The 5-phase crystals of magnesium oxychloride cement have the formula 5Mg(OH)2·MgCl2·8H2O and contribute more to the improved mechanical strength of the cement than any other crystalline phase. The provided composition advantageously produces magnesium oxychloride cement with a predominantly 5-phase crystalline phase. The percentage of magnesium oxychloride cement crystals (i.e., 5-phase magnesium oxychloride cement crystals) in the provided composition can be, for example, about 70% to about 100%, for example, about 70% to about 88%, about 73% to about 91%, about 76% to about 94%, about 79% to about 97%, or about 82% to about 100%. In terms of the lower limit, the percentage of MOC crystals (i.e., 5-phase crystals) can be at least about 70%, for example, at least about 73%, at least about 76%, at least about 79%, at least about 82%, at least about 85%, at least about 88%, at least about 91%, at least about 94%, or at least about 97%.
[0070] III. Bone repair scaffold
[0071] Another aspect of the present disclosure relates to a scaffold that can be used for bone repair. The bone repair scaffold includes a magnesium oxide cement having any composition disclosed herein. Because the scaffold includes a cement having a provided composition, the scaffold has the desired properties of good biocompatibility, easy molding, good degradation, beneficial osteoconductivity, large pore size and high porosity, and excellent mechanical strength. In addition, the specific composition of the provided composition allows the composition to be easily processed into various sizes and various shapes, such as structures that can be used for bone repair applications. In addition, the degradation products of the scaffold promote cell attachment, growth and differentiation, but have almost no side effects on the implanted individual. The favorable scaffold pore size and porosity resulting from the ability of the composition to form Pickering foam allow for good mass transfer of nutrients and other factors required for new bone formation. In addition, the excellent mechanical strength of the scaffold can allow it to maintain the structure of tissue layers during vascularization and bone regeneration.
[0072] In some embodiments, cells are attached to the outer or inner surface of the cement of the provided scaffold. In some embodiments, cells are in the holes of the provided scaffold. Cells can migrate from the individual body to the scaffold, or can be seeded on the scaffold or in the scaffold before or after implantation of the individual. In some embodiments, one or more cell types that promote bone repair are attached to the scaffold or in the scaffold. In some embodiments, mesenchymal stem cells are attached to the scaffold or in the scaffold. In some embodiments, osteoblasts are attached to the scaffold or in the scaffold. In some embodiments, fibroblasts are attached to the scaffold or in the scaffold. In some embodiments, endothelial cells are attached to the scaffold or in the scaffold. In some embodiments, mesenchymal stem cells and osteoblasts are attached to the scaffold or in the scaffold. In some embodiments, mesenchymal stem cells and fibroblasts are attached to the scaffold or in the scaffold. In some embodiments, mesenchymal stem cells and endothelial cells are attached to the scaffold or in the scaffold. In some embodiments, osteoblasts and fibroblasts are attached to the scaffold or in the scaffold. In some embodiments, osteoblasts and endothelial cells are attached to the scaffold or in the scaffold. In some embodiments, fibroblasts and endothelial cells are attached to the scaffold or in the scaffold. In some embodiments, mesenchymal stem cells, osteoblasts and fibroblasts are attached to or within a scaffold. In some embodiments, mesenchymal stem cells, osteoblasts and endothelial cells are attached to or within a scaffold. In some embodiments, mesenchymal stem cells, fibroblasts and endothelial cells are attached to or within a scaffold. In some embodiments, osteoblasts, fibroblasts and endothelial cells are attached to or within a scaffold. In some embodiments, mesenchymal stem cells, osteoblasts, fibroblasts and endothelial cells are attached to or within a scaffold. In some embodiments, mesenchymal stem cells, osteoblasts, fibroblasts and endothelial cells are attached to or within a scaffold.
[0073] IV. Methods of Producing Compositions and Scaffolds
[0074] Another aspect of the present disclosure relates to methods of producing the provided compositions and scaffolds. Specific combinations of the steps of the methods have been shown to impart the advantageous features discussed above to the compositions and scaffolds. The methods generally include forming a mixture of magnesium oxide and one or more surface modifiers dispersed in an aqueous magnesium chloride solution. In some embodiments, the methods further include selecting the properties of the one or more surface modifiers, and the amounts of one or more of the magnesium oxide, surface modifier, magnesium chloride, and water in the aqueous magnesium chloride solution.
[0075] The properties and amount of one or more surface modifiers in the formed mixture can be as discussed above with respect to the provided composition. For example, the formed mixture can contain 0.2wt% to 2wt% of the surface modifier, and the surface modifier can contain one or more short-chain amphiphilic compounds, for example, propyl gallate, caproic acid, gallic acid or any combination thereof. The amount of magnesium oxide in the formed mixture can be as discussed above with respect to the provided composition. For example, the formed mixture can contain 15wt% to 70wt% of magnesium oxide. The amount of magnesium chloride in the formed mixture can be as discussed above with respect to the provided composition. For example, the formed mixture can contain 2wt% to 10wt% of magnesium chloride.
[0076] The method further comprises frothing the mixture under conditions sufficient to generate an aqueous foam. Preferably, the aqueous foam is a Pickering foam stabilized by magnesium oxide particles modified by a surface modifier. The mixture is frothed to produce a foam, generating stable bubbles that define pores of the cement formed by curing the foam in paste form. In some embodiments, the method comprises the step of selecting one or more frothing conditions such that the conditions are selected to be sufficient for forming an aqueous foam.
[0077] The conditions for foaming can include a stirring rate, i.e., for example, from about 6000 rpm to about 20,000 rpm, for example, from about 6000 rpm to about 12,000 rpm, from about 6800 rpm to about 14,000 rpm, from about 7600 rpm to about 16,000 rpm, from about 8600 rpm to about 18,000 rpm or from about 9700 rpm to about 20,000 rpm. With respect to the lower limit, the stirring rate for foaming can be at least about 6000 rpm, for example, at least about 6800 rpm, at least about 7600 rpm, at least about 8600 rpm, at least about 9700 rpm, at least about 11,000 rpm, at least about 12,000 rpm, at least about 14,000 rpm, at least about 16,000 rpm or at least about 18,000 rpm. In terms of upper limits, the stirring rate of foaming can be, for example, at most about 20,000 rpm, for example, at most about 18,000 rpm, at most about 16,000 rpm, at most about 14,000 rpm, at most about 12,000 rpm, at most about 11,000 rpm, at most about 9700 rpm, at most about 8600 rpm, at most about 7600 rpm or at most about 6800 rpm. Higher stirring rates (e.g., greater than about 20,000 rpm) and lower stirring rates (e.g., less than about 6000 rpm) are also contemplated.
[0078] The condition of foaming can include duration, that is, for example, from about 10 seconds to about 60 seconds, for example, from about 10 seconds to about 40 seconds, from about 15 seconds to about 45 seconds, from about 20 seconds to about 50 seconds, from about 25 seconds to about 55 seconds or from about 30 seconds to about 60 seconds.With regard to the lower limit, the duration of foaming can be, for example, at least about 10 seconds, for example, at least about 15 seconds, at least about 20 seconds, at least about 25 seconds, at least about 30 seconds, at least about 35 seconds, at least about 40 seconds, at least about 45 seconds, at least about 50 seconds or at least about 55 seconds.With regard to the upper limit, the duration of foaming can be, for example, at most about 60 seconds, for example, at most about 55 seconds, at most about 50 seconds, at most about 45 seconds, at most about 40 seconds, at most about 35 seconds, at most about 30 seconds, at most about 25 seconds, at most about 20 seconds or at most about 15 seconds. Longer durations (eg, greater than about 60 seconds) and shorter durations (eg, less than about 10 seconds) are also contemplated.
[0079] In some embodiments, the method further comprises the step of mixing one or more additives into the aqueous foam. The identity and amount of the additives and the conditions of mixing are generally sufficient to convert the aqueous foam into a homogenous paste. In some embodiments, the method further comprises the step of selecting the identity of the one or more additives, the independent amount of the one or more additives and / or the one or more mixing conditions such that the selection is sufficient to produce a homogenous paste form of the composition.
[0080] The additive can be any of those disclosed herein. In some embodiments, one or more additives include one or more soluble phosphate compounds, one or more polymers, one or more calcium phosphate cements, additional magnesium oxide, or any combination thereof. The characteristics and amount of one or more soluble phosphate compounds mixed into the aqueous foam as an additive can be as discussed above with respect to the provided composition. For example, the additive can include about 0.2wt% to about 2wt% of a soluble phosphate compound, and the soluble phosphate compound can include phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, or any combination thereof. The characteristics and amount of one or more polymers mixed into the aqueous foam as an additive can be as discussed above with respect to the provided composition. For example, the additive can include about 1wt% to about 10wt% of a polymer, and the polymer can include gelatin, chitosan, or a combination thereof. The characteristics and amount of one or more calcium phosphate cements mixed into the aqueous foam as an additive can be as discussed above with respect to the provided composition. For example, the additive can include about 10wt% to about 35wt% of a calcium phosphate cement, and the calcium phosphate cement can include calcium-deficient hydroxyapatite, hydroxyapatite, brushite, or any combination thereof.
[0081] In some embodiments, the method further comprises the step of curing the homogenous paste to produce cement. The curing conditions are generally sufficient to convert the homogenous paste into a cement having the advantageous properties disclosed herein. In some embodiments, the method further comprises the step of selecting one or more curing conditions such that the selection is sufficient to provide the cement with certain advantageous properties associated with porosity, mechanical strength, or crystalline phase composition disclosed herein.
[0082] Another advantage of the provided method is that curing the composition into a cement form can be easily accomplished at a temperature close to room temperature. Curing conditions can include temperature, i.e., for example, from about 30°C to about 40°C, for example, from about 30°C to about 36°C, from about 31°C to about 37°C, from about 32°C to about 38°C, from about 33°C to about 39°C, or from about 34°C to about 40°C. In terms of lower limits, the curing temperature can be, for example, at least about 30°C, for example, at least about 31°C, at least about 32°C, at least about 33°C, at least about 34°C, at least about 35°C, at least about 36°C, at least about 37°C, at least about 38°C, or at least about 39°C. In terms of upper limits, the curing temperature can be, for example, at most about 40°C, for example, at most about 39°C, at most about 38°C, at most about 37°C, at most about 36°C, at most about 35°C, at most about 34°C, at most about 33°C, at most about 32°C, or at most about 31°C. Higher temperatures (eg, greater than about 40°C) and lower temperatures (eg, less than about 30°C) are also contemplated.
[0083] Curing conditions can comprise the duration, that is, for example, about 24 hours to about 120 hours, for example, about 24 hours to about 82 hours, about 34 hours to about 91 hours, about 43 hours to about 100 hours, about 53 hours to about 110 hours or about 62 hours to about 120 hours.With regard to the lower limit, the duration of curing can be, for example, at least about 24 hours, for example, at least about 34 hours, at least about 43 hours, at least about 53 hours, at least about 62 hours, at least about 72 hours, at least about 82 hours, at least about 91 hours, at least about 100 hours or at least about 110 hours.With regard to the upper limit, the duration of curing can be, for example, at most about 120 hours, for example, at most about 110 hours, at most about 100 hours, at most about 91 hours, at most about 82 hours, at most about 72 hours, at most about 62 hours, at most about 53 hours, at most about 43 hours or at most about 34 hours. Longer durations (eg, greater than about 120 hours) and shorter durations (eg, less than about 24 hours) are also contemplated.
[0084] V. Methods for repairing bone defects
[0085] Another aspect of the disclosure relates to a method for repairing a bone defect in an individual. Specific features of the method have been shown to provide a treatment that benefits from the enhanced properties of the compositions and scaffolds disclosed herein for an individual. The method generally includes implanting a bone repair scaffold into an individual. The bone repair scaffold may be any of those discussed above. The bone repair scaffold may be implanted in an individual near a position of the individual's bone defect, for example, at the site of the bone defect.
[0086] As used herein, the term "individual" refers to a vertebrate, and preferably refers to a mammal. The mammalian individual to which the composition provided is suitable includes, but is not limited to, mice, rats, apes, humans, farm animals, sports animals, and pets. In some embodiments, the individual is a human. In some embodiments, the individual is a male. In some embodiments, the individual is a female. In some embodiments, the individual is an adult. In some embodiments, the individual is a teenager. In some embodiments, the individual is a child. In some embodiments, the individual age is greater than about 10 years old, for example, the age is greater than about 20 years old, the age is greater than about 30 years old, the age is greater than about 40 years old, the age is greater than about 50 years old, the age is greater than about 60 years old, the age is greater than about 70 years old, or the age is greater than about 80 years old. In some embodiments, the individual age is less than about 80 years old, for example, the age is less than about 70 years old, the age is less than about 60 years old, the age is less than about 50 years old, the age is less than about 40 years old, the age is less than about 30 years old, the age is less than about 20 years old, or the age is less than about 10 years old.
[0087] In some embodiments, the method further comprises introducing one or more types of cells into a bone repair scaffold. Attaching cells to the scaffold may include seeding the cells onto the scaffold before or after implantation in an individual. In some embodiments, one or more cell types promoting bone repair are attached to the scaffold. The cell type may be any of those disclosed herein. For example, the cells attached to the scaffold may include mesenchymal stem cells, osteoblasts, fibroblasts, endothelial cells, or any combination thereof.
[0088] The bone defect of an individual can be the result of cancer; a genetic disease; age-related bone loss, e.g., osteoporosis; trauma, e.g., injury; or infection. Thus, the provided bone repair scaffold can be implemented in treatments related to orthopedics, plastic surgery, dentistry, and podiatry. In some embodiments, the bone defect site includes a degenerated or damaged spinal disc, an oral defect, or a maxillofacial defect. Oral and maxillofacial defects that can be repaired with the provided bone repair scaffold include defects in the areas of the head, neck, face, and jaw. Exemplary bone defects include diseased bones, degenerated bones, missing bones, or damaged bones (e.g., fractured or cracked bones).
[0089] In some embodiments, the method also includes assessing the individual to determine the nature of the bone defect to be repaired and the characteristics of the bone repair scaffold suitable for treating the individual. The assessment of the object can include medical imaging (e.g., X-ray imaging, MRI scanning or CT scanning), which can provide the size of the bone defect site and can be used to determine the desired configuration (e.g., size and / or shape) of the bone repair scaffold.
[0090] VI. Exemplary Embodiments
[0091] The following embodiments are considered. All combinations of features and embodiments are considered.
[0092] Embodiment 1: A composition comprising: 15 wt% to 70 wt% magnesium oxide; 2 wt% to 10 wt% magnesium chloride; 0.2 wt% to 2 wt% surface modifier; and 20 wt% to 65 wt% water; wherein the identity and amount of the surface modifier are effective to modify at least a portion of the magnesium oxide to produce particles in the form of Pickering foam sufficient to stabilize the composition.
[0093] Embodiment 2: The embodiment according to embodiment 1, wherein the surface modifier is a short chain amphiphilic compound.
[0094] Embodiment 3: The embodiment according to embodiment 2, wherein the short chain amphiphilic compound is propyl gallate, hexanoic acid or gallic acid.
[0095] Embodiment 4: The embodiment according to any of embodiments 1 to 3, wherein the molar ratio of magnesium oxide to magnesium chloride is 2.5:1 to 15:1.
[0096] Embodiment 5: The embodiment according to any of embodiments 1 to 4, wherein the molar ratio of water to magnesium chloride is 5:1 to 25:1.
[0097] Embodiment 6: The embodiment according to any of embodiments 1 to 5, comprising: 30 wt% to 60 wt% magnesium oxide; 4 wt% to 8 wt% magnesium chloride; 0.4 wt% to 1.3 wt% propyl gallate, hexanoic acid or gallic acid; and 30 wt% to 55 wt% water.
[0098] Embodiment 7: The embodiment according to any of embodiments 1 to 6, further comprising a soluble phosphate compound.
[0099] Embodiment 8: The embodiment according to embodiment 7, wherein the soluble phosphate compound is phosphoric acid, sodium dihydrogen phosphate or disodium hydrogen phosphate.
[0100] Embodiment 9: An embodiment according to embodiment 7 or 8, wherein the concentration of the soluble phosphate compound in the composition is 0.1 wt% to 2 wt%.
[0101] Embodiment 10: The embodiment according to any of embodiments 1 to 9, further comprising gelatin or chitosan.
[0102] Embodiment 11: The embodiment according to embodiment 10, wherein the concentration of gelatin or chitosan in the composition is 1 wt% to 10 wt%.
[0103] Embodiment 12: The embodiment according to any of embodiments 1 to 11, further comprising a calcium phosphate cement, wherein the calcium phosphate cement is calcium-deficient hydroxyapatite, hydroxyapatite or brushite.
[0104] Embodiment 13: The embodiment according to embodiment 12, wherein the concentration of calcium phosphate cement is 10wt% to 35wt%.
[0105] Embodiment 14: The embodiment according to any of embodiments 1 to 6, which has the form of Pickering foam.
[0106] Embodiment 15: The embodiment according to any of embodiments 7 to 13, which has the form of a homogenous paste.
[0107] Embodiment 16: Cement, wherein the cement is formed by curing the homogenous paste of Embodiment 15, and wherein the cement comprises a plurality of pores.
[0108] Embodiment 17: The embodiment described in embodiment 16, wherein at least 10% of the plurality of pores each independently have a diameter greater than 50 μm.
[0109] Embodiment 18: The embodiment described in embodiment 16 or 17, wherein at least 90% of the plurality of pores each independently have a diameter greater than 10 μm.
[0110] Embodiment 19: An embodiment according to any of embodiments 16 to 18, comprising xMg(OH)2·yMgCl2·zH2O crystals, wherein at least 70% of the xMg(OH)2·yMgCl2·zH2O crystals are 5-phase (5Mg(OH)2·MgCl2·8H2O) crystals.
[0111] Embodiment 20: A bone repair scaffold comprising the cement according to any of embodiments 16 to 19.
[0112] Embodiment 21: The embodiment according to embodiment 20, further comprising cells attached to the cement, wherein the cells include mesenchymal stem cells, osteoblasts, fibroblasts, endothelial cells or a combination thereof.
[0113] Embodiment 22: A method for producing magnesium oxychloride cement, the method comprising: forming a mixture of magnesium oxide and a surface modifier dispersed in an aqueous solution of magnesium chloride; and foaming the mixture under foaming conditions sufficient to produce aqueous foam.
[0114] Embodiment 23: An embodiment according to embodiment 22, wherein the aqueous foam is a Pickering foam.
[0115] Embodiment 24: The embodiment according to embodiment 22 or 23, wherein the foaming conditions include a foaming stirring rate of 6000 rpm to 20000 rpm.
[0116] Embodiment 25: The embodiment according to any of embodiments 22 to 24, wherein the foaming conditions include a foaming duration of 10 seconds to 60 seconds.
[0117] Embodiment 26: An embodiment according to any of embodiments 22 to 25, wherein the mixture comprises 15 wt% to 70 wt% magnesium oxide.
[0118] Embodiment 27: An embodiment according to any of embodiments 22 to 26, wherein the mixture comprises 2 wt% to 10 wt% magnesium chloride.
[0119] Embodiment 28: An embodiment according to any of embodiments 22 to 27, wherein the mixture comprises 0.2 wt% to 2 wt% of the surface modifier.
[0120] Embodiment 29: An embodiment according to any of embodiments 22 to 28, wherein the surface modifier is a short chain amphiphilic compound.
[0121] Embodiment 30: The embodiment according to embodiment 29, wherein the short chain amphiphilic compound is propyl gallate, hexanoic acid or gallic acid.
[0122] Embodiment 31: The embodiment according to any of embodiments 22 to 30, further comprising: mixing one or more additives into the aqueous foam under conditions sufficient to produce a homogenous paste, wherein the one or more additives are selected from soluble phosphate compounds, gelatin, chitosan, calcium phosphate cement, and additional magnesium oxide.
[0123] Embodiment 32: The embodiment according to embodiment 31, wherein the homogenous paste comprises soluble phosphate, gelatin or chitosan, and calcium phosphate cement.
[0124] Embodiment 33: An embodiment according to embodiment 31 or 32, wherein the concentration of the soluble phosphate compound in the homogenous paste is 0.2 wt% to 2 wt%.
[0125] Embodiment 34: An embodiment according to any of embodiments 31 to 33, wherein the concentration of gelatin or chitosan in the homogenous paste is 1 wt% to 10 wt%.
[0126] Embodiment 35: An embodiment according to any of embodiments 31 to 34, wherein the concentration of calcium phosphate cement in the homogenous paste is 10 wt% to 35 wt%.
[0127] Embodiment 36: The embodiment of any of embodiments 31 to 35, further comprising: curing the homogenous paste under curing conditions sufficient to produce magnesium oxychloride cement.
[0128] Embodiment 37: The embodiment described in embodiment 36, wherein the curing conditions include a curing temperature of 30°C to 40°C.
[0129] Embodiment 38: An embodiment according to embodiment 36 or 37, wherein the curing conditions include a curing duration of 24 hours to 120 hours.
[0130] Embodiment 39: A method for repairing a bone defect in a subject, the method comprising implanting the bone repair scaffold of embodiment 20 or 21 near the bone defect in the subject.
[0131] Example
[0132] The present disclosure will be better understood in view of the following non-limiting examples.The following examples are for illustrative purposes only and are not intended to limit the scope of the present invention in any way.
[0133] Example 1. Preparation of calcium-deficient hydroxyapatite (CDHA)
[0134] CDHA paste was prepared by directly mixing α-tricalcium phosphate (α-TCP) and 2.5 wt% Na2HPO4 aqueous solution at a ratio of 3 g / mL. The CDHA paste was then transferred to a specific polytetrafluoroethylene (PTFE) mold, sealed, and incubated at 37°C and 100% humidity for 3 days to allow complete curing.
[0135] Example 2. Preparation of magnesium oxychloride cement (MOC) foam (MOCF) derived scaffolds
[0136] Based on the Pickering foaming technique, MOCF-derived scaffolds were prepared according to the recipe shown in Table 1 ( Figure 2 ). In an exemplary procedure, 0.9 g of MgO microparticles and 0.03 g of propyl gallate were dispersed in 1.4 g of MgCl2 solution and immediately frothed by homogenizing at 8000 rpm for 30 s to generate an aqueous foam. Then, an additional 0.6 g of MgO microparticles was added to the obtained foam, followed by the addition of 0.5 wt% H3PO4, 3.5 wt% gelatin B (from cowhide, ~225 bloom) and the prepared CDHA paste at the specified concentration. The resulting combination was gently mixed using a stirring rod to generate a homogenous MOCF paste ( Figure 2 The MOCF paste was then transferred to a specific PTFE mold, sealed, and incubated at 37°C and 100% humidity to allow curing for 3 days ( Figure 7 ).
[0137] Table 1. Recipes used to fabricate MOCF-derived scaffolds.
[0138]
[0139] Example 3. Evaluation of the operational performance of MOCF-derived scaffolds
[0140] The injectability of the MOCF paste of Example 2 prepared was checked using a 5mL syringe. In short, MOCF paste was prepared and immediately extruded from a syringe at a speed of 15mm / min via a material testing system (QTest, ArtisanTechnology Group, USA) until a maximum force of 200N was reached. Extrusion curve (force versus syringe piston displacement) was recorded. The mass of the extruded paste was weighed, and the percentage of the extruded paste was calculated accordingly. In order to evaluate cohesive properties, the newly prepared MOCF paste was directly injected into 37°C phosphate buffered saline (PBS) and the behavior of the paste was observed during the hardening process. The shaping process of the MOCF paste was monitored in a parallel plate geometry of 20mm diameter using a rheometer (Malvern Kinexus Lap+, Malvern Instrument Inc., UK). The newly prepared MOCF paste was loaded into the gap of a 20mm plate and subjected to an oscillation time sweep rheological test. The gap size, strain, and frequency were fixed at 1.5mm, 1%, and 1Hz, respectively. The elastic modulus (G′), viscous modulus (G″) and viscosity (η) were recorded during the measurement and plotted against time (t) to reveal the in situ shaping process of the MOCF paste.
[0141] The results from these studies demonstrate that the provided MOCF scaffolds exhibit good handling properties in their paste state, and thus can be suitable for use as injectable scaffolds in minimally invasive surgery. Fresh MOCF paste can be directly extruded through a syringe immediately after preparation with an extrusion rate of over 99 wt % ( Figure 3 ), indicating satisfactory injectability. The extrusion curves recorded during the injection process reveal the extrusion process of MOCF paste in detail ( Figure 4 ). The overshoot of the curve represents the critical force that allows the paste to flow, and the plateau corresponds to the load required to maintain homogeneous paste flow (about 60 N). The sharp increase in force indicates the end of extrusion, which may be attributed to the mechanical contact between the piston and the bottom of the syringe.
[0142] The setting kinetics of the MOCF pastes were determined by dynamic rheological measurements. It was shown that the elastic modulus (G') was always greater than the viscous modulus (G"), with both G' and G" increasing over time, confirming the predominantly solid-like nature of the pastes ( Figure 5 ). During the measurement, after about 35 minutes, the G' curve and the G" curve gradually reached a plateau. Such a plateau was also seen in the change of the viscosity (η) corresponding to the initial setting time point.
[0143] After injection into PBS, the noodle-like MOCF paste could maintain its shape well without any particle release, indicating excellent cohesive properties ( Figure 6 (i)). Such cohesiveness can be attributed to the presence of small amounts of gelatin. Without being bound by a particular theory, the inventors believe that the gelatin polymer chains act as "glue" to cross-link the inorganic substances within the paste, such as Figure 6 (ii) As shown in the example. After 24 hours of curing, the paste can still remain intact ( Figure 6 (iii) to Figure 6 (iv)). The cross-sectional SEM images of the cured samples also showed the deposition of gelatin polymer on the cell walls ( Figure 6 (v)).
[0144] Example 4. Characterization of the porosity in MOCF-derived scaffolds
[0145] After sputtering with Au nanoparticles, the cross morphology of the cured CDHA scaffolds and MOCF scaffolds of Example 1 and Example 2 was observed using a scanning electron microscope (SEM, Quanta-400, FEI, USA) at an accelerating voltage of 10 kV. The cross region was generated by cutting the sample with scissors. The pore size distribution of the MOCF scaffold was analyzed using SEM and ImageJ software (version 1.52k).
[0146] The results of these studies showed that after full in situ curing, a graded porosity was generated within the MOCF scaffold that allowed for favorable osseointegration during implantation. After full curing in the mold, a cured block of a specific shape ( Figure 7 ). A hierarchical porous structure was constructed in the MOCF scaffold, with pore sizes ranging from tens of micrometers to over 100 micrometers ( Figure 8 Since the additives are introduced after the frothing step, the mixture is then subjected to mechanical agitation ( Figure 2 ), the pores in MOCF become distorted circles. In contrast, conventional CDHA exhibits a dense and non-porous structure, in which nanopores are generated only during cement formation ( Fig. 9 Considering the need for bone integration, the porous MOCF scaffold was shown to be superior to dense CDHA in its ability to guide cell and tissue entry.
[0147] Example 5. Characterization of crystal formation in MOCF-derived scaffolds
[0148] Crystalline phase analysis of the CDHA samples and MOCF samples from Examples 1 and 2 was performed via X-ray diffraction (XRD, SmartLab, Rigaku, Japan) with a scan range of 10° to 65°. Among the phases produced by the aqueous reaction between MgO particles and MgCl2 aqueous solution, for the MgO-MgCl2-H2O ternary system, only 3 phases (3Mg(OH)2·MgCl2·8H2O) and 5 phases (5Mg(OH)2·MgCl2·8H2O) exist at ambient temperature. It is widely accepted that 5-phase crystals make a major contribution to the mechanical integrity of bulk MOC. Therefore, 5-phase crystals are required as the main phase of MOC products with good mechanical properties.
[0149] Observations from the crystal phase analysis of the MOCF sample of Example 2 show that the provided formula ensures the formation of maximum 5-phase MOC crystals in the resulting MOCF scaffold. The XRD spectrum proves that the crystalline 5-phase (MOC-5) is dominant in the MOCF scaffold, in which only a small proportion of Mg(OH)2 ( Fig.10 ). Some residual MgO can also be found in the product, possibly due to the excess feed ratio. In addition, several small peaks observed are attributed to hydroxyapatite (HA), which is caused by the incorporated CDHA. Fig.11 As shown in Figure 5, HA is the main phase in CDHA cement, with a small amount of unreacted α-tricalcium phosphate (α-TCP).
[0150] Example 6. Evaluation of Mechanical Properties of MOCF-Derived Scaffolds
[0151] The mechanical properties of the samples were evaluated by compression testing. Cylindrical MOCF samples and CDHA samples (Φ: 6mm, l: 12mm) were prepared and cured at 37°C and 100% humidity for 3 days. The samples were then compression tested using a universal testing machine (Instron, USA) at a loading rate of 1mm / min. The compressive strength and Young's modulus were then calculated from the strain-stress curve. The mechanical properties of the MOCF scaffolds and CDHA scaffolds after immersion in PBS (pH 7.40) for 8 weeks were also measured by the same protocol. Three samples were measured for each sample.
[0152] The results of these studies indicate that the provided MOCF scaffolds exhibit mechanical properties superior to those of conventional CDHA cements. Mechanical characterization revealed brittle fracture characteristics of both scaffolds ( Fig.12 After 3 days of shaping, both the yield strength and compression modulus of MOCF (about 21.31 MPa; about 0.90 GPa) are significantly higher than those of CDHA (about 15.31 MPa; about 0.53 GPa) ( Fig.13 and Fig.14 ).
[0153] Example 7. Evaluation of the biodegradation properties of MOCF-derived scaffolds
[0154] The degradation behavior of MOCF scaffolds and CDHA scaffolds was examined by accurately immersing weighed samples (Φ: 6 mm, l: 12 mm) in PBS (pH 7.40) at a weight to volume ratio of 0.2 g / mL at 37°C under continuous shaking at 100 rpm. The immersion solution was renewed every 7 days (n=3). During the immersion process, the pH changes and ions (Mg) in the immersion solution were monitored on days 1, 3, 5, and 7. 2+ and Ca 2+ ) concentration. At the specified time point, 300 μL of the soaking solution was quantitatively extracted, and then 300 μL of fresh PBS solution was added to maintain a constant volume. The pH value was measured using a pH meter (Sartorius, Germany), and the ion concentration was determined by an inductively coupled plasma-optical emission spectrometer (ICP-OES, ICPE-9820, Shimadzu, Japan). After soaking for 1 week, 2 weeks, 3 weeks and 4 weeks, the samples were removed from the soaking solution, rinsed with deionized water, and dried at 37 ° C. The weight loss rate of the sample was measured and calculated as a percentage of the initial weight until constant weight was achieved. Then, the sample was immersed in PBS again at the same weight to volume ratio at 37 ° C under continuous shaking. The crystalline phase composition of the sample after 4 weeks of degradation was analyzed using XRD (SmartLab, Rigaku, Japan).
[0155] The mechanical properties of the two scaffolds were re-evaluated after 8 weeks of immersion in PBS solution, showing that the internal structure and mechanical strength of MOCF deteriorated ( Figures 12 to 15 For example, the pore walls in MOCF can be penetrated by corrosive fluids ( Fig.15 ). In contrast, CDHA is mechanically strengthened relative to MOCF after prolonged immersion, with the compressive strength and modulus of CDHA (about 22.91 MPa; about 0.71 GPa) becoming significantly higher than those of MOCF (about 16.17 MPa; about 0.53 GPa). This observed increase in the mechanical strength of the CDHA material may be attributed to the formation of larger blocks in CDHA after immersion ( Fig.15 ). Overall, the mechanical properties of both MOCF and CDHA before and after immersion can match those of cancellous bone, enabling them to maintain the structure of the tissue layer during vascularization and bone regeneration.
[0156] For the MOCF sample, an obvious alkaline transition can be found, and the pH value of the immersion solution reaches 8.65 after 7 days, which is related to the phase transition and dissolution of the 5-phase crystals ( Fig.16 and Fig.19 When exposed to an aqueous environment, the phase 5 compound gradually transforms into slightly soluble Mg(OH)2, which then reacts with relatively high concentrations of Cl - In the presence of MgCl2, it is further converted into water-soluble MgCl2 and releases hydroxyl ions (OH - ), thereby inducing an increase in pH. At the same time, Mg 2+ The concentration level increased due to the dissociation of MgCl2, and the cumulative level reached about 79.6mM ( Fig.17 In addition, about 6 mM calcium ions (Ca) were released in the first week. 2+ ), with the contribution from a small proportion of incorporated CDHA.
[0157] In contrast, there was a slight acidic shift for the CDHA sample, for which the pH value became below 7.00 after 1 week ( Fig.16 ). Almost no ion release was detected during the soaking process. This finding, together with the extremely low weight loss ratio, indicates the poor degradation ability of the relatively non-porous CDHA. On the contrary, after soaking for 2 weeks, a weight gain ( Fig.17 and Fig.18 ), where the increase may be caused by the reprecipitation of HA on the sample surface ( Fig. 20 HA formation also occurs on the MOCF surface ( Fig.19 ), this surface-deposited HA would hinder the degradation process, as seen in the gradual formation of a plateau in the weight loss curve of MOCF (reaching approximately 13 wt% after 4 weeks) ( Fig.18 ).
[0158] These results reveal more favorable degradation kinetics of MOCF scaffolds provided relative to CDHA cement. The favorable properties are due to the better water solubility of MOC and the introduction of micro- and macro-pores through the unique features of the materials and methods disclosed herein. The desired in vitro degradation behavior can mimic the in vivo absorption process to a certain extent, indicating a favorable absorption rate that can achieve complete replacement of the implanted MOCF by regenerated bone tissue.
[0159] Example 8. Cell integration behavior of MOCF-derived scaffolds
[0160] The attachment and adsorption of cells on MOCF scaffolds and CDHA scaffolds were observed by SEM imaging (Quanta-400, FEI, USA). 5 Cells were inoculated on sterile samples (Φ: 8mm, l: 2mm) and then incubated for 1 day and 5 days under cell culture conditions. At the specified time point, the sample was rinsed with PBS (pH 7.40) to remove any non-attached cells or impurities. The cells attached to the sample were then fixed overnight at 4 ° C with 2.5% glutaraldehyde (Sigma) in PBS (10×, pH 7.40). After fixation, the sample was washed 3 times with PBS (10×, pH 7.40) to remove residual cross-linking agents, and then gradient dehydrated with a series of 30 volume %, 50 volume %, 70 volume %, 90 volume %, 95 volume % and 100 volume % ethanol, each lasting 5 minutes. Finally, the sample was soaked in hexamethyldisilazane (HMDS, Sigma) for 15 minutes and then air-dried overnight. Subsequently, after sputtering with Au nanoparticles, the samples were imaged by SEM (Quanta-400, FEI, USA) at 10 kV. The cell extension area was measured using SEM and ImageJ software (version 1.52k).
[0161] Only a small number of cells were able to grow on the CDHA surface ( Fig.21 Furthermore, although cells were able to attach to the CDHA surface by anchoring their pseudopodia to surface cracks, cells attached to CDHA showed a significantly smaller extension area than cells attached to the MOCF surface ( Fig.21 and 22). MC3T3-E1 preosteoblasts can attach well to the MOCF surface, where the cells show a polygonal shape with their stretched filopodia and lamellipodia. In addition, the cells attached to the MOCF showed clear holes into the scaffold on the first day after inoculation. After 5 days, the cell density increased significantly, where almost the entire MOCF surface was covered by cells. These observations reveal the outstanding cell proliferation capacity of the provided MOCF scaffold ( Fig.21 ). The hierarchical porous MOCF scaffolds can better support osteoblast attachment, infiltration and proliferation than non-porous CDHA, and thus can significantly improve cell-material integration.
[0162] Example 9. In vitro osteogenic differentiation associated with MOCF-derived scaffolds
[0163] The osteogenic differentiation of rat bone marrow mesenchymal stem cells (rBMSC) on prepared MOCF scaffolds and CDHA scaffolds was evaluated using sample extracts via an indirect contact method. rBMSCs were isolated from the bone marrow of 6-week-old Sprague Dawley (SD) rats. Cells of passage 2 were used in this experiment. Sample extracts (0.2 g / mL) were collected by soaking the samples in osteogenic induction medium (OIM, cell culture medium supplemented with 10 mM β-glycerophosphate (Sigma), 10 nM dexamethasone (Sigma) and 75 μM L-ascorbic acid (Sigma)) for 24 h, and the extracts with dilution rates of 5 (1:5) and 10 (1:10) were used for the test.
[0164] Briefly, rBMSCs were cultured at 3 × 10 4 The concentration of each cell / well was inoculated in a 24-well plate and cultured for 2 days to allow optimal attachment. Then the cell culture medium was replaced with sample extract to further induce, and OIM was applied to the control group. Sample extract and OIM were updated every 2 days. After induction for 10 days, ARS (Beyotime) staining was carried out according to the manufacturer's instructions, and the sample digitization of staining was used to use a bioscanner (Epson, Japan).
[0165] The osteogenic differentiation of rBMSCs was further evaluated by quantitative real-time polymerase chain reaction (RT-qPCR) to detect the expression of genes related to osteogenesis, including osteopontin (Opn), Runt-related transcription factor 2 (Runx2), and osteoblast-specific transcription factor (Sp7). 5The concentration of 1 cell / well was inoculated in a 6-well plate and cultured for 2 days to allow the cells to fully attach. Then the cell culture medium was replaced with sample extract (1:10) for further induction, and OIM was applied to the control group. Sample extract and OIM were updated every 2 days. After induction for 3 days and 10 days, total RNA was extracted from the cells using TRIzol reagent (Invitrogen). The extracted RNA was quantified using an ND-2000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA). Total RNA from an equal amount (500ng) of each sample was reverse transcribed into cDNA using a cDNA kit (Takara). Then cDNA was amplified with SYBR Green qPCR SuperMix-UDG (Takara) and specific primer sequences (Table 2). qRT-PCR was run on a QuantStudioTM 12K Flex real-time PCR system (Life Technologies, Thermo Fisher Scientific, USA).
[0166] Table 2. Primer sequences used for RT-qPCR
[0167]
[0168] Mineral deposition is a key late sign of osteogenic differentiation. By staining with Alizarin Red S (ARS), the deposited calcium nodules are stained red ( Fig.23 ). The MOCF group showed the most intense red and calcium nodule formation (especially for the 1:10 extract) compared to the CDHA or control groups, indicating enhanced rBMSC osteogenesis. In contrast, the CDHA extract showed an inhibitory effect on rBMSC osteogenesis, where only light red staining could be observed ( Fig.23 ).
[0169] The relative expression of osteogenic genes (Sp7, Runx2, and Opn) in rBMSCs was then analyzed to further determine the osteogenic effect of the MOCF scaffold. After 3 days of induction, although rBMSCs in the MOCF group showed higher expression of Opn and Runx2 than the other two groups, there was no significant difference in the expression levels of the three tested markers among the three groups ( Figure 24 to Figure 26 However, after 10 days of induction, the expression levels of Opn and Sp7 in the MOCF group became significantly upregulated, making the levels significantly higher than those in the CDHA group and the control group ( Fig.24 and Fig.25 These results suggest that MOCF scaffolds have better performance in enhancing osteogenic differentiation compared to CDHA. MOCF degradation can contribute to the inductive microenvironment (which contains osteogenic inductive Mg 2+), which should be conducive to inducing ideal osteogenesis.
[0170] Example 10. In vivo application of MOCF-derived scaffolds for repairing osteoporotic femoral defects in rats
[0171] The in vivo efficacy of the MOCF-derived scaffold provided was further evaluated in the femoral defect model of osteoporotic rats, in which traditional CDHA was used as a control group. First, 12-week-old female SD rats were subjected to ovariectomy (OVX) surgery. OVX surgery was performed under anesthesia by intraperitoneal (ip) injection of a mixture of xylazine, ketamine and saline with a volume ratio of 2:3:3 at a dose of 2ml / kg body weight. In brief, after shaving, the abdominal cavity was entered through a 10mm midline dorsal incision, which allowed the abdominal organs to be pulled to the outside of the abdominal cavity with sterile gauze to expose the ovaries. The ovaries were cut and removed with two ligatures. After 12 weeks, OVX rats were used to establish a femoral defect model. The animal study was divided into two groups: MOCF and CDHA (n=6). After deep anesthesia, the left inner side of the distal femur was exposed. A tunnel bone defect with a diameter of 2mm and a length of 8mm was created by vertically passing through the bone surface by an orthopedic drill cooled with constant saline. Rats were randomly implanted with either cylindrical CDHA scaffolds or cylindrical MOCF scaffolds ( 2mm, 1: 8mm) into the defect. All abdominal muscles were completely sutured in two layers with absorbable sutures, and then the skin was sutured with non-absorbable sutures. TEMGESIC was administered to rats once a day for 3 days. TM (0.05 mg / kg) to minimize the pain suffered after surgery. All rats were housed in the Experimental Animal Center of Prince of Wales Hospital, Hong Kong, under a 12-hour light / dark cycle, an ambient temperature of 18°C to 23°C, and 68% humidity, and received food and water. All animal experimental protocols were approved by the Animal Experimentation Ethics Committee of the Chinese University of Hong Kong.
[0172] At 4 and 12 weeks after surgery, femur samples were collected for X-ray and micro-computed tomography (micro-CT) analysis. The femur was placed in the sagittal and coronal planes and exposed for a few seconds at 30 kV and 700 μA for radiographic imaging (XPERT 80 Cabinet X-ray System, KUBTEC, USA). After fixation, the femur was placed in a sample tube ( 30mm) and scanned with a μCT-40 imaging system (μCT40, Scanco Medical, Brüttisellen, Switzerland). An analysis length of approximately 1.5 mm (100 slides) was used to obtain information about newly formed trabeculae in the defect in addition to bone cement. To limit mineralized tissue, a low-pass Gaussian filter (standard deviation (Sigma) = 0.8, support (Support) = 1) was used to remove background noise, where mineralized tissue was limited to a threshold of 210. The information obtained with this analysis included data on bone mineral density (BMD), bone volume fraction (BV / TV), trabecular number (Tb.N) and trabecular bone separation (Tb.Sp).
[0173] At 4 and 12 weeks post-surgery, favorable bone integration along the defect margins of both MOCF and CDHA could be observed from radiographs, with the MOCF group showing significant bone thickening around the defect margins ( Fig. 27 Representative micro-CT images and corresponding quantitative analysis revealed an enlarged new bone area as well as higher bone volume / total volume (BV / TV) and bone mineral density (BMD) in the MOCF group compared with the CDHA group at 12 weeks post-surgery ( Figures 28 to 30 In addition, at 4 and 12 weeks after surgery, significantly more trabecular bone structures were formed in the MOCF group than in the CDHA group ( Fig.31 ). These results demonstrate that the provided porous MOCF-derived scaffolds have improved regenerative efficacy compared to that of conventional biocement CDHA, showing great potential for clinical translational applications of MOCF-derived scaffolds in the treatment of osteoporotic bone diseases.
[0174] As used herein, the terms "about" and "approximately equal to" when used to modify a numerical value, represent a limited range around that value. If "X" is the value, then "about X" or "approximately equal to X" includes values from 0.90X to 1.10X. Thus, any reference to "about X" represents at least the values X, 0.90X, 0.91X, 0.92X, 0.93X, 0.94X, 0.95X, 0.96X, 0.97X, 0.98X, 0.99X, 1.01X, 1.02X, 1.03X, 1.04X, 1.05X, 1.06X, 1.07X, 1.08X, 1.09X, and 1.10X.
[0175] As used herein, the terms "comprises," "comprising," "having," "containing," and variations thereof are inclusive and open ended, and do not exclude other unstated elements or method steps other than those explicitly stated. As used herein, the phrase "consisting of is closed ended and excludes any element, step, or ingredient not explicitly specified. As used herein, the phrase "consisting essentially of limits the scope of the feature to the specified materials or steps and to those materials or steps that do not materially affect the basic and novel characteristics of the disclosed feature.
[0176] Although the above disclosure has been described in detail by way of example and embodiment for the purpose of clear understanding, it will be appreciated by those skilled in the art that certain changes and modifications may be made within the spirit and scope of the present disclosure (e.g., within the scope of the appended claims). It should also be understood that aspects of the present disclosure and portions of the various described embodiments and features may be combined or interchanged in whole or in part. In the various embodiments described above, as will be appreciated by those skilled in the art, those embodiments relating to another embodiment may be appropriately combined with other embodiments. In addition, it will be appreciated by those of ordinary skill in the art that the foregoing description is exemplary only and is not intended to limit the present disclosure. In addition, each reference provided herein is incorporated herein by reference in its entirety for all purposes, to the same extent as each reference is incorporated herein by reference alone.
Claims
1. A composition comprising: 15 to 70 wt % magnesium oxide; 2wt% to 10wt% magnesium chloride; 0.2 wt % to 2 wt % of a surface modifier; and 20 wt % to 65 wt % of water; The identity and amount of the surface modifier are effective to modify at least a portion of the magnesium oxide to produce particles in the form of Pickering foam sufficient to stabilize the composition.
2. The composition of claim 1, wherein the surface modifier is a short-chain amphiphilic compound.
3. The composition according to claim 2, wherein the short-chain amphiphilic compound is propyl gallate, hexanoic acid or gallic acid.
4. The composition according to any one of claims 1 to 3, wherein the molar ratio of the magnesium oxide to the magnesium chloride is from 2.5:1 to 15:
1.
5. The composition according to any one of claims 1 to 4, wherein the molar ratio of the water to the magnesium chloride is from 5:1 to 25:
1.
6. A composition according to any one of claims 1 to 5, comprising: 30 to 60 wt % magnesium oxide; 4 wt % to 8 wt % magnesium chloride; 0.4 wt % to 1.3 wt % of propyl gallate, caproic acid or gallic acid; and 30 wt% to 55 wt% water.
7. The composition according to any one of claims 1 to 6, further comprising a soluble phosphate compound.
8. The composition of claim 7, wherein the soluble phosphate compound is phosphoric acid, sodium dihydrogen phosphate or disodium hydrogen phosphate.
9. The composition according to claim 7 or 8, wherein the concentration of the soluble phosphate compound in the composition is 0.1 wt% to 2 wt%.
10. The composition according to any one of claims 1 to 9, further comprising gelatin or chitosan.
11. The composition according to claim 10, wherein the concentration of the gelatin or the chitosan in the composition is 1 wt% to 10 wt%.
12. according to the composition described in any one in claim 1 to 11, it further comprises calcium phosphate cement, and wherein said calcium phosphate cement is calcium-deficient hydroxyapatite, hydroxyapatite or brushite.
13. compositions according to claim 12, the concentration of wherein said calcium phosphate cement is 10wt% to 35wt%.
14. A composition according to any one of claims 1 to 6, in the form of a Pickering foam.
15. The composition according to any one of claims 7 to 13, which has the form of a homogeneous paste.
16. Cement, wherein the cement is formed by curing the homogenous paste of claim 15, and wherein the cement comprises a plurality of pores.
17. The cement of claim 16, wherein at least 10% of the plurality of pores each independently have a diameter greater than 50 μm.
18. The cement of claim 16 or 17, wherein at least 90% of the plurality of pores each independently have a diameter greater than 10 μm.
19. The cement according to any one of claims 16 to 18, comprising xMg(OH)2·yMgCl2·zH2O crystals, wherein at least 70% of the xMg(OH)2·yMgCl2·zH2O crystals are 5-phase (5Mg(OH)2·MgCl2·8H2O) crystals.
20. A bone repair scaffold comprising the cement according to any one of claims 16 to 19.
21. The bone repair scaffold of claim 20, further comprising cells attached to the cement, wherein the cells comprise mesenchymal stem cells, osteoblasts, fibroblasts, endothelial cells, or a combination thereof.
22. A method for producing magnesium oxychloride cement, the method comprising: forming a mixture of magnesium oxide and a surface modifier dispersed in an aqueous magnesium chloride solution; as well as The mixture is foamed under foaming conditions sufficient to produce an aqueous foam.
23. The method of claim 22, wherein the aqueous foam is a Pickering foam.
24. The method according to claim 22 or 23, wherein the foaming conditions include a foaming stirring rate of 6000 rpm to 20000 rpm.
25. The method according to any one of claims 22 to 24, wherein the foaming conditions include a foaming duration of 10 seconds to 60 seconds.
26. A method according to any one of claims 22 to 25, wherein the mixture comprises 15 wt% to 70 wt% magnesium oxide.
27. A method according to any one of claims 22 to 26, wherein the mixture comprises 2 to 10 wt% magnesium chloride.
28. The method of any one of claims 22 to 27, wherein the mixture comprises 0.2 wt% to 2 wt% of the surface modifier.
29. The method of any one of claims 22 to 28, wherein the surface modifier is a short chain amphiphilic compound.
30. The method of claim 29, wherein the short chain amphiphilic compound is propyl gallate, hexanoic acid, or gallic acid.
31. The method according to any one of claims 22 to 30, further comprising: One or more additives are mixed into the aqueous foam under conditions sufficient to produce a homogenous paste, wherein the one or more additives are selected from the group consisting of soluble phosphate compounds, gelatin, chitosan, calcium phosphate cement, and additional magnesium oxide.
32. The method of claim 31 , wherein the homogenous paste comprises soluble phosphates, gelatin or chitosan, and calcium phosphate cement.
33. A method according to claim 31 or 32, wherein the concentration of the soluble phosphate compound in the homogenous paste is from 0.2 wt% to 2 wt%.
34. The method according to any one of claims 31 to 33, wherein the concentration of the gelatin or the chitosan in the homogenous paste is 1 wt% to 10 wt%.
35. A method according to any one of claims 31 to 34, wherein the concentration of the calcium phosphate cement in the homogeneous paste is 10 wt% to 35 wt%.
36. The method according to any one of claims 31 to 35, further comprising: The homogenous paste is cured under curing conditions sufficient to produce the magnesium oxychloride cement.
37. The method of claim 36, wherein the curing conditions include a curing temperature of 30°C to 40°C.
38. The method of claim 36 or 37, wherein the curing conditions include a curing duration of 24 hours to 120 hours.
39. A method for repairing a bone defect in an individual, the method comprising implanting the bone repair scaffold of claim 20 or 21 into the individual proximal to the bone defect.